Grenz- und Raumkonstellationen : eine Untersuchung am Beispiel von Yoko Tawadas Talisman (1996) - Schaeffler, Christiane Angela (Stellenbosch : Stellenbosch University, 2017)
ENGLISH ABSTRACT: The works of the Japanese-German writer Yoko Tawada, who started publishing in German in the late 1980s, are widely received in literary studies, mainly under the flag of interculturality and the label migrant literature. But research results show that these categories of analysis are insufficient in terms of understanding Tawada's unique writing style. This study shows that concepts of liminality and space which originate within the context of the transdisciplinary spatial turn, prove to be more productive. Thus the aim of this study is to discuss Yoko Tawada's essay collection Talisman (1996) in relation to theoretical concepts of borders and space, specifically drawing on Yuri Lotman's Sujet-theory and his semiosphere model. With this analytical approach, the functionality of the categories 'border' and 'space' and the extent to which these are involved in the design of the narration are determined. The thesis examines to which extend the constellations of borders and space defined by Lotman shape the global narrative structure of the text as well as other narrative dimensions. The results of this analysis also show that literary space research offers a wide variety of productive categories of analysis that enable the apprehension of spatial heterogeneity in literature and offer insight into the versatile and complex and, above all, the aesthetic production of space in literature, thus allowing a new aesthetic reading of Talisman.